Criterios básicos para la elaboración de un curriculum de Física y Química - Seminario de Física y Química del ICE, Equip (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The primary aim of this paper is to know the choice of Physics and Chemistry teachers concerning some basic criteria which should be considered when designing a curriculum, and to contrast them with the implications arising from educational research.